An Analysis of The Offense of Unpleasant Action in Article 335 Paragraph (1) of The Indonesian Criminal Code - Xavier Nugraha; Kusuma Wardani Raharjo; Ahmad Ardhiansyah; Alip Pamungkas Raharjo (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
The Constitutional Court as the guardian of the constitution and the guardian of human rights has the duty to ensure that the Law does not contradict the constitution and does not violate human rights. One of the manifestations of this can be seen in the Constitutional Court Decision Number 1 / PUU-X / 2013, where the Constitutional Court removed the element